International human trafficking: Measuring clandestinity by the tructural equation approach - Alexandra Rudolph; Friedrich Schneider (Johannes Kepler University of Linz, Department of Economics, 2013)
Worldwide human trafficking (HT) is the third most often registered international criminal activity, ranked only after drug and weapon trafficking. The aim of the paper is to measure the extent of HT inflows to destination countries. It proposes the application of the Multiple Indicators Multiple Causes (MIMIC) structural equation model in order to include potential causes and indicators in one model and generate an index of the intensity of HT in destination countries. Thus, we account for the unobservable nature of the crime as well as for visible aspects that both shape the extent of it. By including both dimensions of the trafficking process the model is applied over a period of ten years. The resulting measure orders 142 countries between 2000 and 2010 according to their potential of being a destination country based on characteristics of the trafficking process. The results are that OECD countries are the most likely destination countries while developing countries are less likely.
Keywords: C39; F22; K42; K49; 330; Human trafficking; MIMIC models; latent variable; structural equation models